A Study on the Empowering Effect of Digital Economy Industrial Policies on Common Prosperity in China’s Urban and Rural Areas - Duan , Weihua; Yang, Jie; Asif, Muhammad; Zhang, Mengyan (Al-Qanṭara, 2025)
Guided by the goal of common prosperity, China's urban-rural income gap has narrowed continuously but remains significantly wide. With the intensive implementation of policies such as the "Overall Plan for Building a Digital China," the digital economy has emerged as a new engine driving urban-rural integration. Using panel data from 283 prefecture-level cities in China from 2012 to 2023, this study empirically analyzes the intrinsic relationship and operational mechanisms between digital economy industrial policies and common prosperity in urban and rural areas. The results indicate that the enabling effect of digital economy industrial policies on urban-rural common prosperity exhibits significant regional and digital transformation heterogeneity. Specifically, these policies demonstrate stronger enabling effects in the eastern, central, and northeastern regions and areas with high levels of digital transformation. Mechanism analysis indicates that digital economy industrial policies drive shared prosperity through two pathways: stimulating entrepreneurial activity and enhancing resource allocation efficiency. Based on these findings, this study proposes a three-pronged policy approach: optimizing the digital industrial ecosystem through dual measures, channeling entrepreneurial vitality to precisely nurture the fertile ground of shared prosperity, and pursuing optimal resource allocation solutions through coordinated efforts. These recommendations aim to provide theoretical insights for advancing shared prosperity between urban and rural areas.